2021
DOI: 10.1007/s11846-021-00475-8
|View full text |Cite
|
Sign up to set email alerts
|

Does it pay more to be green in family firms than in non-family firms?

Abstract: The contradictory empirical evidence about whether the effect of companies' environmental investments on financial results is positive, negative or not significant has been explained by the different conditions and contexts that facilitate or hinder the ability to generate a win–win situation. This explanation has gradually led the academic debate to consider the factors and conditions that moderate such a relationship. In this document, we analyse the relevant but scarcely studied moderating effect of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 89 publications
(137 reference statements)
1
21
0
2
Order By: Relevance
“…Traditionally, in developing countries, when enterprises transform products and services into profits, managers rarely care about the negative impact of their decisions and behaviors on the environment ( Shahzad et al, 2021 ). With the emergence of a large number of ecological and environmental problems, managers were increasingly forced to consider the impact of their organizations on the natural environment ( Garcés-Ayerbe et al, 2022 ). As a result, green management appeared.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, in developing countries, when enterprises transform products and services into profits, managers rarely care about the negative impact of their decisions and behaviors on the environment ( Shahzad et al, 2021 ). With the emergence of a large number of ecological and environmental problems, managers were increasingly forced to consider the impact of their organizations on the natural environment ( Garcés-Ayerbe et al, 2022 ). As a result, green management appeared.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…By the 1990s, as ecological values gradually formed, the green market emerged, and economic profit created by the emerging green market linked the interests of entrepreneurship and the social environment, scholars found that being green did not place a burden on the enterprise. It was more likely to enable enterprises to have the opportunity to develop their advantageous resources and positive performance impact ( Garcés-Ayerbe et al, 2022 ). The view that entrepreneurs are not environmentally conscious or not concerned regarding the environment became outdated.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…L'evidència empírica contradictòria sobre si l'efecte de les inversions ambientals de les empreses sobre els resultats financers és positiu, negatiu o no significatiu, ha estat explicada per les diferents condicions i contextos que faciliten o dificulten la capacitat de generar una situació d'obtenir beneficis. Aquesta explicació ha portat de mica en mica el debat acadèmic a considerar els factors i condicions que moderen aquesta relació (Gárces-Ayerbe et al, 2021).…”
Section: Revisió De La Literatura I Hipòtesis De Treballunclassified
“…La evidencia empírica contradictoria sobre si el efecto de las inversiones ambientales de las empresas sobre los resultados financieros es positivo, negativo o no significativo ha sido explicada por las diferentes condiciones y contextos que facilitan o dificultan la capacidad de generar una situación de obtener beneficios. Esta explicación ha llevado paulatinamente al debate académico a considerar los factores y condiciones que moderan tal relación (Gárces-Ayerbe et al, 2021).…”
Section: Revisión De La Literatura E Hipótesis De Trabajounclassified